The good, the bad & the beagle - Burns, Catherine Lloyd (New York Farrar Straus Giroux, 2014)
Shy, eleven-year-old Veronica Louse Morgan of New York CIty is not happy about having to attend Randolf School for Girls, but by the end of her first year she not only has some new friends, she may have finally convinced her parents that she is ready to own a dog.
720L
102275
Keywords: Dogs -- Juvenile fiction; Family life -- New York (State) -- New York; Schools; Friendship; Humorous stories; Family -- Parents; Social Issues; Humorous fiction; Juvenile Fiction